Osaru no Jōji aisukurīmu daisuki - Perez, Monica (Iwanami Shoten, 2011)
George is looking for a way to beat the summer heat. Swimming, running through sprinklers, a glass of lemonade--none is able to help George cool off! What George really wants is a sweet, cold treat from the ice cream truck! But will he ever catch it?
In japan. Schr.
Keywords: Curious George (Fictitious character) / Juvenile fiction; Monkeys / Juvenile fiction; Ice cream, ices, etc / Juvenile fiction; Summer / Juvenile fiction; Affen; Speiseeis; Bilderbuch